ChemInform Abstract: CuI‐Catalyzed Cross‐Coupling of Terminal Alkynes with Dialkoxycarbenes: A General Method for the Synthesis of Unsymmetrical Propargylic Acetals. Issue 2 (January 2015) - Xiao, Tiebo; Zhang, Ping; Xie, Yang; Wang, Jun; Zhou, Lei
Abstract Oxadiazolines (I) can be generally employed as a source of dialkoxycarbenes generated by thermal decomposition.